Training for performance improvement: A practical guide to training practitioners and educators - Habi Raphael J. M.; Gellejah Sabina P. M. (Mzumbe University, 2026)
This book is designed for those who want to acquire the skills and techniques of training and who also want to be effective practitioners, educators and trainers. The book is organised in six chapters. The first chapter gives an overview of training and education concepts. The second chapter looks at learning as a crucial ingredient to training. The third chapter focuses on performance improvement. The fourth chapter deals with development of a training programme while chapter five discusses how to conduct the training. The last chapter is on evaluation of a training programme. At the end of each chapter there are reflective questions to stimulate some food for thought and enhance the learning